Society for Maternal-Fetal Medicine Consult Series #52: Diagnosis and management of fetal growth restriction - Martins, Juliana Gevaerd; Biggio, Joseph R.; Abuhamad, Alfred (American journal of obstetrics and gynecology, 2020)
Fetal growth restriction can result from a variety of maternal, fetal, and placental conditions. It occurs in up to 10% of pregnancies and is a leading cause of infant morbidity and mortality. This complex obstetrical problem has disparate published diagnostic criteria, relatively low detection rates, and limited preventative and treatment options. The purpose of this Consult is to outline an evidence-based, standardized approach for the prenatal diagnosis and management of fetal growth restriction. The recommendations of the Society for Maternal-Fetal Medicine are as follows: (1) we recommend that fetal growth restriction be defined as an ultrasonographic estimated fetal weight or abdominal circumference below the 10th percentile for gestational age (GRADE 1B); (2) we recommend the use of population-based fetal growth references (such as Hadlock) in determining fetal weight percentiles (GRADE 1B); (3) we recommend against the use of low-molecular-weight heparin for the sole indication of prevention of recurrent fetal growth restriction (GRADE 1B); (4) we recommend against the use of sildenafil or activity restriction for in utero treatment of fetal growth restriction (GRADE 1B); (5) we recommend that a detailed obstetrical ultrasound examination (current procedural terminology code 76811) be performed with early-onset fetal growth restriction (<32 weeks of gestation) (GRADE 1B); (6) we recommend that women be offered fetal diagnostic testing, including chromosomal microarray analysis, when fetal growth restriction is detected and a fetal malformation, polyhydramnios, or both are also present regardless of gestational age (GRADE 1B); (7) we recommend that pregnant women be offered prenatal diagnostic testing with chromosomal microarray analysis when unexplained isolated fetal growth restriction is diagnosed at <32 weeks of gestation (GRADE 1C); (8) we recommend against screening for toxoplasmosis, rubella, or herpes in pregnancies with fetal growth restriction in the absence of other risk factors and recommend polymerase chain reaction for cytomegalovirus in women with unexplained fetal growth restriction who elect diagnostic testing with amniocentesis (GRADE 1C); (9) we recommend that once fetal growth restriction is diagnosed, serial umbilical artery Doppler assessment should be performed to assess for deterioration (GRADE 1C); (10) with decreased end-diastolic velocity (ie, flow ratios greater than the 95th percentile) or in pregnancies with severe fetal growth restriction (estimated fetal weight less than the third percentile), we suggest weekly umbilical artery Doppler evaluation (GRADE 2C); (11) we recommend Doppler assessment up to 2–3 times per week when umbilical artery absent end-diastolic velocity is detected (GRADE 1C); (12) in the setting of reversed end-diastolic velocity, we suggest hospitalization, administration of antenatal corticosteroids, heightened surveillance with cardiotocography at least 1–2 times per day, and consideration of delivery depending on the entire clinical picture and results of additional evaluation of fetal well-being (GRADE 2C); (13) we suggest that Doppler assessment of the ductus venosus, middle cerebral artery, or uterine artery not be used for routine clinical management of early- or late-onset fetal growth restriction (GRADE 2B); (14) we suggest weekly cardiotocography testing after viability for fetal growth restriction without absent/reversed end-diastolic velocity and that the frequency be increased when fetal growth restriction is complicated by absent/reversed end-diastolic velocity or other comorbidities or risk factors (GRADE 2C); (15) we recommend delivery at 37 weeks of gestation in pregnancies with fetal growth restriction and an umbilical artery Doppler waveform with decreased diastolic flow but without absent/reversed end-diastolic velocity or with severe fetal growth restriction with estimated fetal weight less than the third percentile (GRADE 1B); (16) we recommend delivery at 33–34 weeks of gestation for pregnancies with fetal growth restriction and absent end-diastolic velocity (GRADE 1B); (17) we recommend delivery at 30–32 weeks of gestation for pregnancies with fetal growth restriction and reversed end-diastolic velocity (GRADE 1B); (18) we suggest delivery at 38–39 weeks of gestation with fetal growth restriction when the estimated fetal weight is between the 3rd and 10th percentile and the umbilical artery Doppler is normal (GRADE 2C); (19) we suggest that for pregnancies with fetal growth restriction complicated by absent/reversed end-diastolic velocity, cesarean delivery should be considered based on the entire clinical scenario (GRADE 2C); (20) we recommend the use of antenatal corticosteroids if delivery is anticipated before 33 6/7 weeks of gestation or for pregnancies between 34 0/7 and 36 6/7 weeks of gestation in women without contraindications who are at risk of preterm delivery within 7 days and who have not received a prior course of antenatal corticosteroids (GRADE 1A); and (21) we recommend intrapartum magnesium sulfate for fetal and neonatal neuroprotection for women with pregnancies that are <32 weeks of gestation (GRADE 1A).